How wrong can you be? Can a simple spreading formula be used to predict worst-case underwater sound levels? - Duncan, Alexander; Parsons, Miles (The Australian Acoustical Society, 2011)
Several simple spreading laws have been proposed to allow estimates of underwater sound levels to be made without the complication of numerical modelling. Underwater acoustic propagation depends in an involved way on a number of geometric and environmental parameters, including source, receiver and water dept11, and water column and seabed acoustic properties. As a result, there are many scenarios in which the use of these formulae lead to large errors. However, there would be a place for a formula that could provide an upper limit on received sound levels in a particular situation as this would enable sound sources that had a very low probability of posing an environmental hazard to be quickly eliminated from further consideration. Such a formula is proposed in this paper and its bounds of applicability are explored by comparison with numerical model results for several scenarios.